Implications of Sediment Properties on Phosphorus Availability to the Selenastrum capricornutum in Urmia Lake Rivers. Issue 8 (21st June 2022) - Arfania, Hamed; Samadi, Abbas; Asadzadeh, Farrokh; Sepehr, Ebrahim; van der Zee, Sjoerd
Abstract: Increasing anthropogenic loading of phosphorus (P) threatens aquatic ecosystems. The bioavailability of P in sediments for algal growth depends on several physiochemical properties. This study is aimed at selecting the best chemical extraction method to characterize P‐availability for the alga Selenastrum capricornutum . Principal component analysis of the data identified two components that cover 79.3% of the total variation, and these components are dominated by particle size distribution, active calcium carbonate equivalence, and electical conductivity (EC). Many of the considered extractions are positively correlated with each other, with the exception being Bray‐II. The sediments of some rivers have an Olsen‐extractable P higher than 20 mg kg −1, that is considered a threshold value above which the aquatic environment may become negatively affected. The average rank order of P extraction by single extractants is: Colwell > Mehlich III > 0.1 m NaOH > Olsen > Morgan > Soltanpour and Schwab (AB‐DTPA) > Bray II. The Colwell‐extractable P concentrations of sediments varies from 1.44 to 88.0 mg kg −1 . The Cowell extractant significantly correlates with algal growth ( r 2 = 0.92, P < 0.001) and gives a rough estimate of the amount of bioavailable P in sediments. Abstract : Phosphorus (P) availability in the downstream river sediments has resulted in harmful algal bloom. In this study, bioavailable sedimentary P is estimated using routine tests. P extracted by the Colwell method (0.5 m NaHCO3, 16 hours extraction time) is significantly correlated with Selenastrum capricornutum population when sediments are added to the culture medium ( r 2 = 0.92, P < 0.001).